PERANCANGAN BERORIENTASI OBJEK APLIKASI EDUGAME BELAJAR BAHASA INGGRIS BERBASIS FLASH ACTION SCRIPT 2.0 - Akhmad Zulkifli; Faizal Farabi (RJOCS (Riau Journal of Computer Science), 2018)
English learning using text lacks appeal for children. The use of multimedia will make the learning process fun because children interact directly with moving pictures and sound. Edugame application presents different nuances and experiences for children of primary school age in understanding English as well as interacting with computer applications. This app is designed with an Object-Oriented approach that uses UML. A game that is Quiz Game devoted according to the needs of users of the Institute of English Course. This application is implemented using Action Script 2.0 programming language and Adobe Flash software. This application is very interactive and can be used as a teaching tool in learning English or used independently by the user